A model for sharing of students' assessment resources among schools using cloud computing platform - Saidu, Abdullahi Nababa; Universiti Sultan Zainal Abidin . Faculty of Informatics and Computing (2015)
Cloud computing becomes an important technology in today's IT industry. It is a technology which delivers a pool of configurable computing resources to the users. This research proposed a model for sharing students' assessment resources (examinations and exercise) among schools using cloud computing platform known as Cloud Based Assessment Resource Sharing System (CARSS). Students' assessments are used in making decision about what to teach and how well students have learned. The insufficient systems for sharing of students' assessment resources, poor extended pattern of assessment sharing system and inadequate network and computing facilities become an issue among schools management. The aim of the research is to address these crucial issues. The sharing of assessment resources is modelled based on Multi Person Prisoner's Dilemma and Peer-Approved incentive mechanism that gives justifications among users in the resource utilization. The concept of Software as a Service is adopted to make the CARSS system available on the cloud. Based on the proposed model, CARSS prototype is developed and deployed into cloud using OpenStack architecture. The proposed model is evaluated using questionnaire instrument which is based on four attributes of usability metrics. The results showed that the model usability achieved 79.28% of effectiveness, 81.35% of efficiency, 91.8% of learnability and 93.18% of satisfaction. The overall average percentage of the system usability is 86.40%. The survey results show that the system is efficient and effective. Also CARSS system could save the cost of buying,computing and storage infrastructure since all the assessment resources are cloud base.
1. Introduction -- 2. Literature review -- 3. Research methodology -- 4. Discussion and result analysis -- 5. Conclusion
Thesis (Degree of Master of Science in the Faculty of Informatics and Computing) - Universiti Sultan Zainal Abidin, 2015
Includes bibliographical references (leaves 96-101)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Informatics and Computing -- Dissertations; Cloud computing; Educational tests and measurements; Dissertations, Academic